E-commerce in Kerala: A platform for business enterprises to venture into the global market and boost economic growth - Silpa Sasankan (International Journal of Management, Technology And Engineering, 2018)
In 2016, Kerala became the first digital state of India. A consumer state, Kerala has a high potential for the electronic-commerce (e-commerce) market. The Government of Kerala is taking various measures to implement and facilitate the adoption of e-commerce to improve the state’s economic situation. The policies and tax laws are being addressed to encourage small and medium enterprises, traders/merchants to adapt to the online marketplace and to use the opportunities to expand the business globally. E-commerce is a business platform that is mediated by the use of the internet. Across India, the increasing use of electronic devices and increased penetration of the internet are contributing to the growth of e- commerce. Different features like retailer’s dynamic website, proper and accurate description and a better quality image of products, good quality and prompt delivery of products, 24x7 customer service with reduced turnaround time, product disclosure with clear terms of purchase and replacement, pre- and post-sale services are driving more customers towards online shopping. This paper examines the growth and challenges and the overall scenario of e-commerce in Kerala.